Complete Chloroplast Genome, Distribution, and Pharmacological Activities Pogostemon: A Mini Review - Fahira, Cut Nathasya; Harnelly, Essy; Zumaidar (Postgraduate, University of Mataram, 2024)
Pogostemon Desf. is the largest genus in the Pogostemoneae (Lamiaceae). The plastid genomes of Pogostemon species ranged from 151,824 to 152,707 bp in length and comprise 114 genes including 80 protein coding genes, 30 tRNA genes, and four rRNA genes. Pogostemon is found mostly in tropical and subtropical areas of Asia. P. cablin as one of the commercial species of the genus Pogostemon has various abundant pharmacological activities, such as anti-hypertension, anti-diabetic, anti-cancer, anti-inflammatory, anti-aging, etc. This review studied the complete chloroplast genome of Pogostemon, distribution of Pogostemon, and pharmacological activity of P. cablin. Online literature searches were carried out to compile the article. The following search terms were used to find online publications: Pogostemon, distribution of Pogostemon, complete chloroplast genome of Pogostemon, and pharmacological activity of P. cablin plants in PubMed (Medline) and Web of Science. Additionally, several assessments of prior and present data from the Pogostemon and P. cablin research publication were included into one review.